A Systematic Review: Cost-Effectiveness of SGLT2 Inhibitors versus DPP-4 Inhibitors as Add-on to Metformin - Izzatu Al Hanifiyah; Yunita Nita; Libriansyah; Achmad Ridwan (Universitas Airlangga, 2025)
Background: The prevalence of type 2 diabetes mellitus (T2DM) is increasing worldwide. Sodium-glucose cotransporter-2 inhibitors (SGLT2i) and dipeptidyl peptidase-4 inhibitors (DPP-4i) are two second-line therapy alternatives for T2DM patients inadequately controlled with metformin. Objective: This study aimed to systematically review the cost-effectiveness of combining metformin+SGLT2i vs metformin+DPP-4i for T2DM treatment. Methods: A systematic search was conducted in PubMed, Scopus, and ScienceDirect for articles published between 2015-2025, using predefined keywords and following the PRISMA and PICOS frameworks (P: T2DM patients uncontrolled on metformin monotherapy; I: Metformin+SGLT2i therapy; C: Metformin+DPP-4i therapy; O: Cost, clinical outcomes (HbA1c% reduction), Incremental Cost-Effectiveness Ratio (ICER) values, Quality Adjusted Life Years (QALY); S: Study with cost-effectiveness analysis design). Additional studies were identified through reference screening. Eligible articles were independently reviewed and assessed for reporting quality using the CHEERS-2022 standards. Results: Five studies met the inclusion criteria. Considerable heterogeneity was observed with mean patient ages ranging from 55-61 years old and baseline HbA1c levels from 7.9%-9.4%. The studies were conducted in the US, UK, Mexico, and Greece, all funded by the pharmaceutical industry, and used economic models. Despite these differences, all studies consistently demonstrated that combining metformin+SGLT2i was more cost-effective than metformin+DPP-4i. SGLT2i improved the quality of life by 0.032–0.04 QALYs, reduced hypoglycemia, and provided additional benefits for patients with cardiovascular risk, although it was associated with higher initial costs. Conclusion: This review showed that the combination of metformin+SGLT2i was more cost-efficient and effective in managing T2DM than the combination of metformin+DPP-4i.